TINJAUAN YURIDIS TERHADAP ADANYA WANPRESTASI DALAM MEMORANDUM OF UNDERSTANDING PT. MATAHARI ANUGERAH PERKASA DENGAN CV. PONOROGO DI KOTA MEDAN - FRANS WASTON (PREMISE LAW JURNAL, 2015)
Business development encouraging the increasing number of foreigners coming to Indonesia to do business has made many new changes in the practice of business law in Indonesia. In the field of law, this Memorandum of Understanding is new so the special definite regulation to regulate it is not yet available, and for this purpose, the authorized official should make law intended to enact a regulation of legislation to facilitate the life of the nation such as politics, economy and the law itself. The purpose of this study was to analyze 1. How Memorandum of Understanding is legally regulated in Indonesia if one of the parties breaches the contract during the implement process of the Memorandum of Understanding, 2. How the dispute occured due to the breach of contract found in the Memorandum of Understanding made by PT. Matahari Anugerah Perkasa and CV. Ponorogo is settled, and 3. What legal sanctions should be imposed to the party that do not perform his/her obligations as agreed in the Memorandum of Understanding.The data for this analytical prescriptive study with empirical juridical approach were obtained through documentation study and interviewing related respondents. The data obtained were analyzed through descriptive data analysis. The conclusion drawn from the result of this study is that I. If there is a breach of contract in the Memorandum of Understanding, it is legally regulated based on the content of the Memorandum of Understanding, meaning, if the contents of the Memorandum of Understanding meet the elements found in Article 1320 of the Indonesian Civil Codes, the regulation refers to the Article 1338 of the Indonesian Civil Codes stating that it can be applied as a law for those who made the Memorandung of Understanding which means that the agreement stated in the Memorandum of Understanding has a legal power in accordance with Article 1338 paragraph (1) of the Indonesian Civil Codes. Yet, if the agreement stated in the Memorandum of Understanding was made as a letter of intent (memorandum of agreement) only, the legal sanction for it is only a moral sanction, 2. The dispute occured due to the breach of contract found in the Memorandum of Understanding made by PT. Matahari Anugerah Perkasa and CV. Ponorogo was settled by way of concensus and deliberation, and 3. The breach of contract found in the Memorandum of Understanding made by PT. Matahari Anugerah Perkasa and CV. Ponorogo requires CV. Ponorogo to pay a compensation for Rp. 500,000,000.00 (five hundred million rupiahs) to PT. Matahari Anugerah Perkasa for the breach of contract it made. Keywords: Memorandum of Understanding, Breach of Contract